Intertwining worlds: The dynamics of linguistic religion and religious language - Mohammad, Ali Reza (Journal of Religion and Linguistics, 2024)
Linguists and scholars in Iran have overlooked the interaction between language and religion. The correlation between language and religion is substantial among individuals. This study aims to determine whether language serves religion or if there is a distinct category known as religious language. The purpose of this study is to explore further and analyze various perspectives on the relationship between language and religion. We devised a fundamental structure of conversation guidelines based on the works "Religious Language" by Peter Donovan and "Religion and the Making of Society" by Charles Davis. This study examines the argumentation topic through three primary points. The first portion of the text provides a concise overview of the essential information regarding the epistemological and ontological elements of language and religion. A comprehensive analysis of many papers and books has been conducted to extract diverse viewpoints on the interplay between language and religion. The disparities in this region were elucidated by describing both the real and fictitious aspects, as well as the meaningful and meaningless distinctions. The subsequent part explores several tactics employed in theological texts and religious languages and their influence on the dissemination of religious ideology. The primary contention in this part revolves around the capacity of religious language to incite and evoke emotions in individuals. The final section of the paper examines the objectives and intentions of religious declarations and texts by analyzing their discourses using Van Dijk's framework of ideological discourse analysis.